1996
DOI: 10.1109/63.484419
|View full text |Cite
|
Sign up to set email alerts
|

Direct control strategies based on sensing inductance in switched reluctance motors

Abstract: The stator winding current commutation timing is the central subject of switched reluctance motor control. The direct use of coil inductance information for current commutation is introduced in this paper. The drawbacks of position-based commutation, in the presence of drifting electrical parameters, are overcome by using the instantaneous coil inductance information. Algorithms to optimize torque using this approach are also presented in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…In a broad perspective, the measurement methods can be categorised as off-line and on-line methods. In case of off-line measurements, the recorded data of applied phase voltage, using either a single-phase AC supply [13,14] or a pulsed DC source [15][16][17][18][19], and phase currents are obtained from the repeated experiments performed by locking the rotor of an SRM at different angular positions. They are further processed either analytically or by means of a software subroutine in a computer [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a broad perspective, the measurement methods can be categorised as off-line and on-line methods. In case of off-line measurements, the recorded data of applied phase voltage, using either a single-phase AC supply [13,14] or a pulsed DC source [15][16][17][18][19], and phase currents are obtained from the repeated experiments performed by locking the rotor of an SRM at different angular positions. They are further processed either analytically or by means of a software subroutine in a computer [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In case of off-line measurements, the recorded data of applied phase voltage, using either a single-phase AC supply [13,14] or a pulsed DC source [15][16][17][18][19], and phase currents are obtained from the repeated experiments performed by locking the rotor of an SRM at different angular positions. They are further processed either analytically or by means of a software subroutine in a computer [13][14][15][16][17][18][19]. The precision of the methods [13][14][15][16][17][18][19] depends on the locking mechanism and the resolution of angular rotation of the rotor in each step of measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by monitoring current waveforms and computing the rate change of the currents, detection of rotor position in stepping and switched motors has been proposed [5]. In addition, several modulation techniques and a mutually induced voltage measuring technique have been presented [6][7][8][9]. These methods mentioned above are very good; however, they were applied in switched reluctance motors, not SRMs.…”
Section: Introductionmentioning
confidence: 99%
“…Control techniques with self-tuning capability are essential to maintain an optimal performance of a SRM drive, in the presence of parameter variations. It has been shown that parameter variations can alter the inductance profile to a significant extent [3]. Since the control of SRM is essentially based on the inductance profile, it necessitates an on-line self-tuning control strategy for optimum performance.…”
Section: Introductionmentioning
confidence: 99%